MENUMBUHKAN KEPEMIMPINAN ANAK DI SEKOLAH DASAR NEGERI 14 BANDA ACEH - Marantika, Laura Oktaviany; Mardhatillah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Leadership is an important social skill to develop from an early age in children. The learning process that supports leadership development in elementary schools has an important role in shaping children's character and organizational abilities. In this era of globalization, leadership abilities are no longer the exclusive domain of adults or state leaders. Leadership is now seen as a skill that can be developed from an early age. This research aims to document and analyze the efforts of Banda Aceh State Elementary School 14 in cultivating children's leadership through special programs. This research uses a qualitative approach method with descriptive research type. Through a series of interviews, information was obtained about understanding the concept of child leadership, student participation in leadership activities, concrete programs implemented, the role of parents and teachers, visible positive impacts, as well as challenges faced and strategies for overcoming them. The interview results show that the school implements a holistic approach in developing students' social skills, responsibility and decision-making abilities. Programs such as leadership training and collaborative projects are designed to give students hands-on experience. The role of parents and teachers is recognized as an important element in supporting children's leadership development. Visible positive impacts include increased student self-confidence and communication skills. Schools overcome challenges by engaging a team of teachers, collaborating with parents, and conducting ongoing evaluations.